1976
DOI: 10.1007/bf00292953
|View full text |Cite
|
Sign up to set email alerts
|

Absence of short period interspersion of repetitive and non-repetitive sequences in the DNA of Drosophila melanogaster

Abstract: A sensitive search has been made in Drosophila melanogaster DNA for short repetitive sequences interspersed with single copy sequences. Five kinds of measurements all yield the conclusion that there are few short repetitive sequences in this genome: () Comparison of the kinetics of reassociation of short (360 nucleotide) and long (1,830 nucleotide) fragments of DNA; 2) reassociation kinetics of long fragments (2,200 nucleotide) with an excess of short (390 short nucleotide) fragments; 3) measurement of the siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
1

Year Published

1977
1977
1997
1997

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(33 citation statements)
references
References 30 publications
1
31
1
Order By: Relevance
“…Robertson (11) found mariner-like elements in 15% of 400 insect species from eight orders using degenerated PCR from conserved amino acid regions of the putative transposase. Previous studies have shown that the D. pulchellus, E. vuilleti, and A. mellifera genomes contain few interspersed repeated sequences, suggesting that transposable elements might be eliminated by male haploidy (7,8). Those data indicate that transposable elements with no direct deleterious effects on insect viability might not be eliminated by selection in male haploids during evolution.…”
Section: _ X ĩ G a C C G A T A C A A C A M A -R C C A C A T T G A C Cmentioning
confidence: 75%
See 1 more Smart Citation
“…Robertson (11) found mariner-like elements in 15% of 400 insect species from eight orders using degenerated PCR from conserved amino acid regions of the putative transposase. Previous studies have shown that the D. pulchellus, E. vuilleti, and A. mellifera genomes contain few interspersed repeated sequences, suggesting that transposable elements might be eliminated by male haploidy (7,8). Those data indicate that transposable elements with no direct deleterious effects on insect viability might not be eliminated by selection in male haploids during evolution.…”
Section: _ X ĩ G a C C G A T A C A A C A M A -R C C A C A T T G A C Cmentioning
confidence: 75%
“…The genomes of two parasitoid wasps, Diadromus pulchellus and Eupelmus vuilleti (7), and the honey bee, Apis mellifera (8), contain few interspersed repeated sequences corresponding to transposable elements. This might be due to the elimination of deleterious transposable elements in haploid males.…”
mentioning
confidence: 99%
“…aegypti genome is organized in a ''short period interspersion pattern'' in which the single-copy DNAs are partitioned into small blocks by repetitive elements (40,47). In contrast, the majority of the D. melanogaster genome is organized in a ''long period interspersion pattern'' (43,48) in which single-copy DNAs are less interrupted by the interspersion of long repetitive elements. The presence of highly repetitive MITE-Like elements in Ae.…”
Section: Mite-like Elements and The Size And Organization Of Eukaryotmentioning
confidence: 98%
“…bryos and larvae. Dr Ken Jones (University of Edinburgh) kindly provided a sample of DNA isolated as in [20]. This DNA had been purified by isopycnic centrifugation on CsCl gradients [21].…”
Section: Preparation Of Divamentioning
confidence: 99%